PENGEMBANGAN PESAN-PESAN GIZI SEIMBANG DALAM PUGS YANG LEBIH PRAKTIS DIGUNAKAN PETUGAS GIZI LAPANGAN - Afriansyah, Nurfi; Mudjianto, Trintrin T.; Hidayat, Tjetjep S.; Hermina, Hermina; Luciasari, Ema; Fuada, Noviati (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2012)
DEVELOPMENT OF NUTRITIONAL MESSAGES IN THE DIETARY GUIDELINES FOR INDONESIANS THAT MORE PRACTICAL TO BE USED BY FIELD NUTRITION STAFFS. Background: Nutritional messages in the Dietary Guidelines should be simple and relatively few in numbers to obtain maximum awareness and understanding among the users. Some observational studies indicated that nutritional messages of the Dietary Guidelines for Indonesians (PUGS) were considered complex so they were difficult for 'field' nutrition staffs to understand them. Objectives: The purpose of this study is to explore and modify the nutritional messages that are considered complex by 'field' nutrition staffs to become the understandable and practical nutritional messages. Methods: A capacity building method has been developed to explore and modify the nutritional messages that are considered complex. This process involved seven participants: four 'field' nutrition staffs (two PUSKESMAS nutrition staffs from Medan City and two from Deli Serdang District) and three nutrition staffs from the Health Office of Medan City and Deli Serdang District, North Sumatera Province. Nutritional messages were modified based on the inputs of capacity building forum. Results: The nutritional messages of number 2-3-4 in PUGS were difficult messages to be understood by nutrition staffs. The modified 2-3-4 messages by nutrition staffs were still somewhat difficult for them. The final result was the ten modified nutritional messages which were, according to nutrition staffs, more understandable and practical. Keywords: Nutritional messages, Dietary Guidelines for Indonesians (PUGS), nutrition staffs